How Experiences Affect Psychological Responses During Supervised Fasting: A Preliminary Study - Ma, Qianying; Yang, Chao; Wu, Ruilin; Wu, Manrui; Liu, Wenjun; Dai, Zhongquan; Li, Yinghui (Frontiers in Psychology, 2021)
As an unusual event, fasting can induce strong physiological and psychological reactions, but there is still no clear understanding of how previous fasting experience affects people’s responses to current fasting. This study aimed to investigate the influence of previous fasting experience on participants’ basic physiological and psychological responses in a fasting experiment that was conducted under intensive medical monitoring. In a 22-day experiment that was divided into 4 phases (3-day Baseline; 10-day Complete Fasting; 4-day Calorie Restriction; and 5-day Recovery phases), a total of 13 persons participated; they were divided into a group with prior fasting experience (Experienced: N = 6) and a group without prior fasting experience (Newbie: N = 7). The results indicated that there were no group differences in physiological responses (i.e., weight, glucose and ketone body); however, differences in psychological states were observed, with the Newbie group showing more negative psychological states overall throughout the experiment (i.e., higher appetite, more negative mood states, more stress, less vitality and less recovery resources). Hence, previous fasting experience may be a buffer against negative feelings during current fasting. For this reason, it is important to consider the fasting experiences as a vital factor for future research.